A Study of the Components of Medical Ethics in Ancient Persian Literature and Its Comparison with Modern Medical Ethics - A Ebrahimi Mehr (Armaghane Danesh Bimonthly Journal)
Background & aim: Findings from ancient Persian literary texts indicate that the issue of professional medical ethics and the correct and logical relationship between a doctor and a patient has not been hidden from the eyes of writers and poets. In addition to the ethical advice of famous physicians, such as Ismail Jorjani, Ibn Sina, Razi, and other ancient Persian literary works have similarly addressed this issue and provided valuable ethical advice to physicians. The society of literature, using their creative and poetic nature, have recounted the relationship between a physician and a patient, sometimes in the form of stories and sometimes in explicit language. Although the field of medical knowledge and technology has made significant progress in recent decades and modern medical ethics has replaced traditional ethics, it seems that some acts and rights related to patients in the contemporary era are the moral heritage contained in ancient works, and in order to develop and complete ethical principles, we can return to this valuable heritage and support. Therefore, the aim of the present study was to determine and examine the components of medical ethics in ancient Persian literary texts and to compare them with modern medical ethics.